Effect of isothermal annealing on yield anisotropy of AZ31 Mg alloy bars processed by ambient extrusion - Zong-Yuan Cheng; Tao Fang; Yi-Song Wang; Huan-Huan Chen; Jin-Hua Peng; Liang-Yu Chen; Zhen Zhang; Sheng Lu (Journal of Materials Research and Technology)
Magnesium and its alloys show strong mechanical anisotropy due to their hexagonal close-packed structure. This paper processed ambient extrusion and subsequent annealing on AZ31 magnesium alloy bars to investigate the effect of working hardening and texture weakening on yield anisotropy of magnesium alloy. After ambient extrusion, yield strength on different loading direction are improved due to working hardening. ED-yield strength has the highest increment because work hardening has a higher effect on prismatic slip. Then, yield anisotropy becomes stronger with the increase of extrusion train. During annealing, static recrystallization occurs firstly in {101‾1} twinning zones and producing recrystallized grains with random orientation. With the growth of recrystallized grains, basal fiber texture is weakened gradually. Such weak basal texture can promote the activation of basal slip when loading along ED, so ED-yield strength shows a high decrement. On this way, the yield anisotropy in AZ31 magnesium alloy bars is weakened through ambient extrusion and subsequent annealing.